2020
DOI: 10.1017/ice.2019.339
|View full text |Cite
|
Sign up to set email alerts
|

Hand hygiene promotion delivered by change agents—Two attitudes, similar outcome

Abstract: Objective:To assess the effect of peer-identified change agents (PICAs) compared to management-selected change agents (MSCAs) on hand hygiene behavior in acute care.Design:Randomized-controlled study.Setting:Two internal medicine wards of a public, university-affiliated, tertiary-care hospital in Malaysia.Methods:We randomly allocated 2 wards to hand hygiene promotion delivered either by PICAs (study arm 1) or by MSCAs (study arm 2). The primary outcome was hand hygiene compliance using direct observation by v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 21 publications
0
23
0
2
Order By: Relevance
“…Two studies (11%) that used a single intervention involved the removal of elements of hygiene procedures to measure the effect of their absence on compliance [60,69]. These included introducing a personal- [67] Medical/surgical ward (1) Direct (52,065) Derde et al [35] Adult ICUs ( 13) Direct (41,558) Chhapola and Brar [79] Neonatal ICU ( 1) Direct (28,726) Mu et al [82] Whole organization (1) Direct (27,852) Aghdassi et al [43] Medical/surgical wards ( 20) Direct (21,424) Reisinger et al [44] Medical/surgical wards þ ICU (11) Direct (13,195) Stewardson et al [61] Whole organization (1) Direct (12,579) Rodriguez et al [87] Adult ICU (1) Direct (10,429) Saharman et al [84] Adult ICUs (2) Direct (7187) Kuruno et al [72] Adult ICU ( 1) Direct (6050) Lee et al [62] Medical/surgical wards (2) Direct (4895) Medeiros et al [89] Adult ICU ( 1) Direct (4837) Labi et al [40] Whole organization (2) Direct (4296) Primary healthcare centre (13) Chakravarthy et al [41] Adult ICUs (3) Direct (3612) Tschudin-Sutter et al [80] Medical/surgical wards ( 12) Direct (2923) Santoaningsih et al [77] Medical/surgical wards ( 5) Direct (2766) Stevenson et al [83] Whole organization ( 1) Direct (2654) Su et al [86] Medical/surgical wards ( 5) Direct (2079) Schmitz et al [37] Medical/surgical wards ( 4) Direct (2000) Diefenbacher et al [65] Medical/surgical wards ( 4) Direct (1894) Apisarnthanarak et al [55] Adult ICUs ( 6) Direct (1872) Fouad and Eltaher [71] Medical/surgical ward (1) Direct (1374) Teesing et al [90] Nursing homes (…”
Section: Hand Hygiene Compliance Interventionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies (11%) that used a single intervention involved the removal of elements of hygiene procedures to measure the effect of their absence on compliance [60,69]. These included introducing a personal- [67] Medical/surgical ward (1) Direct (52,065) Derde et al [35] Adult ICUs ( 13) Direct (41,558) Chhapola and Brar [79] Neonatal ICU ( 1) Direct (28,726) Mu et al [82] Whole organization (1) Direct (27,852) Aghdassi et al [43] Medical/surgical wards ( 20) Direct (21,424) Reisinger et al [44] Medical/surgical wards þ ICU (11) Direct (13,195) Stewardson et al [61] Whole organization (1) Direct (12,579) Rodriguez et al [87] Adult ICU (1) Direct (10,429) Saharman et al [84] Adult ICUs (2) Direct (7187) Kuruno et al [72] Adult ICU ( 1) Direct (6050) Lee et al [62] Medical/surgical wards (2) Direct (4895) Medeiros et al [89] Adult ICU ( 1) Direct (4837) Labi et al [40] Whole organization (2) Direct (4296) Primary healthcare centre (13) Chakravarthy et al [41] Adult ICUs (3) Direct (3612) Tschudin-Sutter et al [80] Medical/surgical wards ( 12) Direct (2923) Santoaningsih et al [77] Medical/surgical wards ( 5) Direct (2766) Stevenson et al [83] Whole organization ( 1) Direct (2654) Su et al [86] Medical/surgical wards ( 5) Direct (2079) Schmitz et al [37] Medical/surgical wards ( 4) Direct (2000) Diefenbacher et al [65] Medical/surgical wards ( 4) Direct (1894) Apisarnthanarak et al [55] Adult ICUs ( 6) Direct (1872) Fouad and Eltaher [71] Medical/surgical ward (1) Direct (1374) Teesing et al [90] Nursing homes (…”
Section: Hand Hygiene Compliance Interventionsmentioning
confidence: 99%
“…All of these studies used an educational intervention delivered by staff to staff. In the study by Lee et al, staff were identified as HH change agents [62], while Ng et al [78] used an ultraviolet hand scanner glow germ solution to demonstrate the proper HH technique. In the study by Mukherjee et al, surgical internees attended repeated phases of an educational intervention if they did not use the perfect HH technique.…”
Section: Hand Hygiene Compliance Interventionsmentioning
confidence: 99%
See 3 more Smart Citations